432 3-year results of the phase 2 randomized trial for talimogene laherparepvec (T-VEC) neoadjuvant treatment plus surgery vs surgery in patients with resectable stage IIIB-IVM1a melanoma. (9th November 2020) - Dummer, Reinhard; Gyorki, David; Hyngstrom, John; Berger, Adam; Conry, Robert; Demidov, Lev; Chan, Edward; Radcliffe, Hoi-Shen; Faries, Mark; Ross, Merrick
Abstract : Background: Neoadjuvant immunotherapies and targeted therapies for advanced melanoma are an active area of investigation. This is the first clinical trial of an approved oncolytic viral immunotherapy as a neoadjuvant treatment in advanced melanoma and the largest randomized controlled neoadjuvant trial including all types of resectable regional metastases to date. Previously published 2-year primary analysis results reported improved recurrence-free survival (RFS, HR 0.66, P=0.038) and overall survival (OS, HR 0.49, P=0.050) for neoadjuvant T-VEC plus surgery vs immediate surgery in resectable stage IIIB-IVM1a melanoma patients. 1 Here, we report the 3-year interim analysis results. Methods: Patients with resectable stage IIIB-IVM1a melanoma and ≥ 1 injectable cutaneous, subcutaneous, or nodal lesions were randomized 1:1 to receive 6 doses/12 weeks of neoadjuvant T-VEC then surgery (Arm 1) vs immediate surgical resection (Arm 2). T-VEC was administered until surgery, no remaining injectable tumors, or intolerance. RFS was defined as time from randomization to the first of local, regional, or distant recurrence, or death, where patients who did not receive surgery were imputed as events at baseline. Key secondary and exploratory endpoints include safety, an RFS sensitivity analysis that censored events at the start of subsequent anticancer therapy, OS, and event-free survival (EFS), defined as time from randomization to disease progression that precludes surgery, or local, regional or distant recurrence post-surgery, or death from any cause, whichever occurs first. All P values are descriptive. NCT02211131 . Results: As of April 30, 2020, median follow-up for all patients was 41.3 months. For Arm 1 vs. Arm 2, the 3-year KM estimates of RFS were 46.5% vs. 31.0% (HR 0.67, P=0.043). In the RFS sensitivity analysis that removed the potential effect of subsequent anticancer therapy on RFS, the 3-year Kaplan-Meier (KM) estimates of RFS were 49.1% for Arm 1 and 22.9% for Arm 2 (HR 0.60, P=0.022). The 3-year KM estimates of EFS were 50.3% for Arm 1 and 32.7% for Arm 2 (HR 0.58, P=0.015). For OS, the 3-year KM estimates were 83.2% for Arm 1 and 71.6% for Arm 2 (HR 0.54, P=0.061). No new safety signals were detected. Conclusions: At 3-year follow up, we continued to observe improved RFS and OS and observed improved EFS with neoadjuvant T-VEC plus surgery compared with surgery alone. These results build upon the prior 2-year results to support the treatment effect of neoadjuvant T-VEC on advanced resectable melanoma. The final analysis will occur at 5 years. Acknowledgements: The authors thank the investigators, patients, and study staff who are contributing to this study. The study was sponsored and funded by Amgen Inc. Medical writing support was provided by Christopher Nosala (Amgen Inc.). Trial Registration: NCT02211131 Ethics Approval: The study was approved by all institutional ethics boards. Reference: Dummer R, Gyorki DE, Hyngstrom J, et al. Primary 2-year (yr) results of a phase II, multicenter, randomized, open-label trial of efficacy and safety for talimogene laherparepvec (T-VEC) neoadjuvant (neo) treatment (tx) plus surgery (surg) vs surg in patients (pts) with resectable stage IIIB-IVM1a melanoma. Ann Oncol 2019;30;V903.